Portable Ladder Safety: Summarizing OSHA Requirements: AE569/AE569, 4/2022 - Gorucu, Serap; Brown, Charles; Lehtola, Carol (EDIS, 2022)
This publication summarizes the parts of the OSHA Standard 1910.23 that apply to the portable ladders that are frequently used in agricultural operations. Written by Serap Gorucu, Charles Brown, and Carol Lehtola, and published by the UF/IFAS Department of Agricultural and Biological Engineering, April 2022.